Analysis of Strategies to Improve Human Resource Performance in Employees Technical Implementation Unit Paser Belengkong Animal Health Center - Romyansyah, Romyansyah; Jamal, Muh.; Hafel, Muhlis (Pancasila International Journal of Applied Social Science, 2024)
The Paser Belengkong Animal Health Center Technical Implementation Unit (Puskeswan) was established in the context of developing animal health services and to support the prevention and control of strategic and contagious animal disease (zoonosis) programs. The concept of UPT Puskeswan Paser Belengkong is to be the spearhead of animal health services in its working area which is modern, advanced, effective, efficient, safe, comfortable. Therefore, to support the implementation of achieving these goals, it is necessary to know the extent of performance conditions and determine strategies for improving the performance of human resources for animal health services at UPT Puskeswan in Paser Belengkong District. Data analysis in this study uses SWOT analysis. SWOT stands for S: Strength, W: Weakness, O: Opportunity, T: Threts (threat). This SWOT analysis is basically a strategy by taking into account the organization's internal consisting of strengths and weaknesses and external conditions consisting of opportunities and threats. Internal conditions are conditions that are controllable (can be influenced/controlled), while external conditions are more uncontrollable (cannot be influenced/controlled). Based on the results of the SWOT research, it was concluded that the strategy for improving HR performance at UPT Puskeswan Paser Belengkong is a strategy: (1) HR arrangement according to work capacity; (2) Continue education (CE) or continuing education; (3) Increase promotion to the public.